The Dangers of Youth Football. Issue 6 (November 2017) - Beal, Judy A.
Abstract : Pediatric providers working in emergency rooms treat more than 200, 000 children ages 5–18 for sports-related head injuries each year. Approximately 3 million youth are playing tackle football today in the United States. Our pediatric nursing expert, Dr. Judy Beal, explains evolving evidence about the dangers of youth tackle football.